Characteristics of redox processes, thiol system and mucin in the tear fluid in type 2 diabetics (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To assess the characteristics of redox processes, thiol system and mucin in the tear fluid in patients with T2DM.Material and Methods: Thirty type 2 diabetics (60 eyes) with ocular surface changes were included in the study. Patient eyes were divided into groups based on the bulbar conjunctival changes corresponding to the Nelson grade: group 1 (33 eyes with Nelson grade 2 to 3 changes in the bulbar conjunctiva) and group 2 (27 eyes with Nelson grade 0 to 1 changes in the bulbar conjunctiva). Tear lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G6PDH), malate dehydrogenase (MDH), and glutathione peroxidase (GPX) activities and tear mucin, reduced glutathione (GSH) and oxidized glutathione (GSSG) levels were determined by routine techniques.Results: We found alterations in tear redox reactions (LDH, G6PDH and MDH activities), GPX activity and thiol status (GSH and GSSG levels) in the setting of cytological conjunctival changes (i.e., different Nelson grades of squamous metaplasia) in type 2 diabetics. In addition, we found decreased tear mucin levels, which could be associated with alterations in the above biochemical processes and/or cytological conjunctival changes in patients of these groups.Conclusion: Determining characteristics of tear redox reactions, glutathione system and mucin level can be considered as a method for monitoring the course of ocular surface disease based on the grade of squamous metaplasia of the bulbar conjunctiva in type 2 diabetics.
Keywords: type 2 diabetes mellitus; redox processes; ocular surface; thiol status; mucin; tear; conjunctival impression cytology; Nelson grades; squamous metaplasia